Answer: y=-2x+7
Step-by-step explanation:
The equation of a line
[tex]\displaystyle\\\boxed {\frac{x-x_1}{x_2-x_1}=\frac{y-y_1}{y_2-y_1} }[/tex]
(8,-9) (-4,15)
x₁=8 x₂=-4 y₁=-9 y₂=15
[tex]\displaystyle\\\frac{x-8}{-4-8} =\frac{y-(-9)}{15-(-9)} \\\\\frac{x-8}{-12}=\frac{y+9}{15+9} \\\\\frac{x-8}{-12}=\frac{y+9}{24}[/tex]
Let's multiply both parts of the equation by 24:
[tex]\displaystyle\\\frac{24(x-8)}{-12} =y+9\\\\-2(x-8) =y+9\\\\-2x+16=y+9 \\\\-2x+16-9=y+9-9\\\\-2x+7=y\\\\Thus,\\\\y=-2x+7[/tex]